Eksistensi modal sosial pedagang pasar tradisional terhadap kesejahteraan dalam perspektif ekonomi Islam - Fitria, Nia; Hasimi, Diah Mukminatul; Malik, Anas (Nur Science Institute, 2025)
Traditional markets are important in society's economy, especially for small traders. The increasing competition with modern retail and various economic challenges require traders to have the right strategies to improve their welfare. One of the factors that contributes to maintaining the stability and sustainability of traders' businesses is social capital, which includes social networks, trust, and norms that prevail in the trading environment. From an Islamic economic perspective, social capital can strengthen the principles of justice, transparency, and cooperation. Using an Islamic economic approach, this study examines how social capital contributes to improving the welfare of traders in Tugu Market, Bandar Lampung. The research method used is qualitative descriptive, with data collection techniques through observation, interviews, and documentation. The results show that social capital influences three main aspects: economic, social, and spiritual. From the economic side, cooperation and good relationships among traders are highlighted. In the social aspect, the culture of mutual assistance strengthens relationships and solidarity among traders. Finally, from the spiritual aspect, the application of Islamic economic principles in business is emphasised. Therefore, policies that support the revitalisation of markets are needed to optimise the sustainable improvement of traders' welfare.